Developmental stage‐dependent switching in the neuromodulation of vertebrate locomotor central pattern generator networks. Issue 1 (20th November 2019) - Hachoumi, Lamia; Sillar, Keith T.
Abstract: Neuromodulation plays important and stage‐dependent roles in regulating locomotor central pattern (CPG) outputs during vertebrate motor system development. Dopamine, serotonin and nitric oxide are three neuromodulators that potently influence CPG outputs in the development of Xenopus frog tadpole locomotion. However, their roles switch from predominantly inhibitory early in development to mainly excitatory at later stages. In this review, we compare the stage‐dependent switching in neuromodulation in Xenopus with other vertebrate systems, notably the mouse and the zebrafish, and highlight features that appear to be phylogenetically conserved.